The biotechnology of lactic acid bacteria with emphasis on applications in food safety and human health - Daly, Charles; Davis, Ruth (Agricultural Research Centre of Finland, 1998)
Ruoka-aineiden käyttäminen maitohappobakteerien avulla on yksi vanhimmista säilöntämenetelmistä. Näiden teollisuustuotannossakin merkittävien maitohappobakteerien geneettisten ja fysiologisten ominaisuuksien tutkimuksessa on viime vuosina edistytty merkittävästi. Yksi maitohappobakteerien tärkeä ominaisuus on niiden kyky tuottaa mikrobeille vastustuskykyisiä yhdisteitä. Mikrobeille vastustuskykyiset yhdisteet kiinnostavat aiempaa enemmän, koska niitä voidaan käyttää elintarviketeollisuudessa kemiallisten säilöntäaineiden sijaan. Kuluttajat ovat yhä enemmän tietoisia ruoan ja terveyden välisestä yhteydestä. Viime aikaiset tutkimustulokset tukevat oletuksia, joiden mukaan maitohappobakteereilla on probioottisia, terveyttä edistäviä, ominaisuuksia. Lisäksi tällä hetkellä selvitetään eräiden maitohappobakteerien kykyä toimia suun kautta nautittavien rokotteiden elävinä kuljetusvektoreina.

Fermentation of various foodstuffs by lactic acid bacteria (LAB) is one of the oldest forms of biopreservation practised by mankind. In recent years, significant advances have been made in elucidating the genetic and physiological basis of key LAB traits involved in these industrially significant processes. One important attribute of many LAB is their ability to produce antimicrobial compounds called bacteriocins. Interest in these compounds has grown substantially due to their potential usefulness as natural substitutes for chemical food preservatives in the production of foods with enhanced shelflife and/or safety. There is growing consumer awareness of the link between diet and health. Recent scientific evidence supports the role of probiotic LAB in mediating many positive health effects. In addition, some LAB are currently being assessed for their ability to act as live delivery vectors in the development of new oral vaccines.
Keywords: Re; probiootit; maitohappobakteeri; ruoka; biopreservation; functional foods; probiotics; LAB-vaccines